Language Practices of Indigenous Children and Youth : the Transition from Home to School. - Wigglesworth, Gillian (Palgrave studies in minority languages and communities., 2017)
This text explores the experiences of Indigenous children and young adults around the world as they navigate the formal education system and wider society. Profiling a range of different communities and sociolinguistic contexts, this book examines the language ecologies of their local communities, schools and wider society and the approaches taken by these communities to maintain children's home languages. The authors examine such complex themes as curriculum, translanguaging, contact languages and language use as cultural practice. In doing so, this edited collection acts as a first step towards developing solutions which address the complexity of the issues facing these children and young people.